Circular Economy of Source-Separated Organic Waste in New York City - Santunu Barua (International Journal Science and Technology, 2026)
New York City (NYC) generates more than one million tons of compostable organic waste annually, most of which is still landfilled, contributing to greenhouse gas emissions and resource loss. Objective: This review aims to examine the circular economy potential of source-separated organic waste (SSOW) in NYC, with a primary focus on the residential curbside organics program. Method: This study uses a systematic literature review approach by synthesizing peer-reviewed articles, government reports, program documents, and policy records related to composting, anaerobic digestion (AD), community composting, life-cycle assessment (LCA), and NYC’s regulatory framework. Findings: The findings show that landfilling organic waste produces nearly 400 kg CO₂e per tonne, whereas composting generates net negative emissions of approximately −41 kg CO₂e per tonne and dry AD for renewable natural gas yields −36 to −2 kg CO₂e per tonne. Although NYC’s mandatory curbside composting program was fully enforced in April 2025 and collected more than 30,000 tons of organics in 2024, residential capture rates remain below 5%, indicating persistent challenges in infrastructure, public education, contamination control, and multi-family building compliance. Implications: These results imply that an integrated system combining composting, AD, and community composting can improve resource recovery, climate performance, and social participation. Originality: The originality of this review lies in its integrated analysis of technical, environmental, regulatory, and community dimensions of SSOW management within a single circular economy framework, providing a policy-relevant perspective for advancing zero-waste strategies in dense metropolitan contexts.